Late Archean geologic history of the Nain Province, North River-Nutak map area, Labrador, and its tectonic significance - Van Kranendonk, Martin; Helmstaedt, Herwart (Geoscience Canada, 1990)
Summary The high-grade gneisses of the Archeannian Province were formed through Early and Late Archean orogenlc cycles. Late Archean structural development consistedof pre-thermal-peak isoclinal folding and thrusting in allochthonous Upemavik supra-crustal rocks, followed by regional, recum-bent, isoclinal folding and upright refolding ofthe Upernavik suite and reworked Early Archean gneisses under amphibolite- to granulite-facies conditions. Style and sequence of the Late Archean structures closely resemble those described by previous workers from the Early Archean gneiss complex ofthe North Atlantic craton, from Precambriangreenstone belts, and from Phanerozoic orogenic belts, suggesting that no principal differences exist in the structural evolution of these types of terrain.